KAMPANYE KESETARAAN GENDER DALAM INDUSTRI MUSIK GLOBAL OLEH SPOTIFY: Studi Kasus Spotify Equal - Nidya Arum Dhamar Pinasti; Januari Pratama Nurratri Trisnaningtyas (Journal Publicuho, 2025)
This inequality is evidenced by the long-standing male dominance in the industry, where male musicians are consistently favoured over their female counterparts. Consequently, the percentage of female musicians remains substantially lower than that of male musicians. Addressing this issue, Spotify, one of the largest companies in the global music industry, has initiated support for female musicians worldwide through its campaign titled Spotify EQUAL. Through this initiative, Spotify has committed to addressing gender inequality issues in the global music industry. This research focuses on analyzing the efforts undertaken by Spotify through its gender equality campaign, Spotify EQUAL. The study employs feminist theory as a social movement framework underlying gender equality campaigns. Additionally, the authors utilize the concept of digital activism, which encompasses four strategies, to analyze the campaign efforts conducted by Spotify and its Ambassador in the Spotify EQUAL program. This research adopts a qualitative descriptive approach, explaining the analytical result of the efforts implemented in the Spotify EQUAL gender equality campaign.